Merging of Game Principles and Learning Strategy using Apps for Science Subjects to Enhance Student Interest and Understanding (Sains Humanika, 2013)
The popularity of digital games is undeniable. There are numerous studies on digital games based learning (DGBL) which demonstrate the increased interest in digital games among students. Conversely, there has been a significant decline of interest in learning science. DGBL merges principles and strategies from the game and education fields. It is believed the combination of these two fields would enhance interest in learning science as well as assist students to understand highly conceptual subjects such as Chemistry. However, researchers face challenges to integrate principles of games into educational theories which are often too broad to be implemented in DGBL development. As such, this conceptual paper tries to discuss the potential of merging game principles and learning strategies in DGBL for teaching science concepts.
Keywords: Digital game based learning; conceptual framework; game principle; learning strategy